FIGURE 1 in The genus Contracaecum Raillet & Henry (Nematoda: Anisakidae): host and geographical distribution on Neotropical and Antarctic species - Garbin, Lucas E.; Diaz, Julia I.; Servián, Andrea; Fusaro, Bruno; Navone, Graciela T. (Zenodo, 2023)
FIGURE 1. Distribution of Neotropical and Antarctic Contracaecum species indicated by reference numbers according to Table 1. Published as part of Garbin, Lucas E., Diaz, Julia I., Servián, Andrea, Fusaro, Bruno & Navone, Graciela T., 2023, The genus Contracaecum Raillet & Henry (Nematoda: Anisakidae): host and geographical distribution on Neotropical and Antarctic species, pp. 43-62 in Zootaxa 5256 (1) on page 56, DOI:10.11646/zootaxa.5256.1.3, http://zenodo.org/record/7745326